Systematic Analysis of microRNA Biomarkers for Diagnosis, Prognosis, and Therapy in Patients With Clear Cell Renal Cell Carcinoma - Cheng, Guiyun; Li, Mengru; Ma, Xiaoyu; Nan, Fangmei; Zhang, Lu; Yan, Zhongyi; Li, Huimin; Zhang, Guosen; Han, Yali; Xie, Longxiang; Guo, Xiangqian (Frontiers in Oncology, 2020)
The ever-increasing morbidity and mortality of Clear Cell Renal Cell Carcinoma (ccRCC) urgently demands updated biomarkers. MicroRNAs (miRNAs) are involved in diverse biological processes such as cell proliferation, differentiation, apoptosis by regulating their target genes’ expression. In kidney cancers, miRNAs have been reported to be involved in tumorigenesis, and to be the diagnostic, prognostic, and therapeutic response biomarkers. Here, we performed a systematic analysis for ccRCC-related miRNAs as biomarkers by searching keywords in the NCBI PubMed database, and found 121 miRNAs as diagnostic biomarkers, 28 miRNAs as prognostic biomarkers, and 81 miRNAs as therapeutic biomarkers in ccRCC. miRNA-21, miRNA-155, miRNA-141, miRNA-126 and miRNA-221, as significantly differentially expressed miRNAs between cancer and normal tissues, play extensive roles in the cell proliferation, differentiation, apoptosis of ccRCC. GO and KEGG enrichment analysis of these miRNAs’ target genes through Metascape showed these target genes enriched in Protein Domain Specific Binding (GO:0019904). In this paper, we identified highly specific miRNAs in the pathogenesis of ccRCC and explored their potential applications for diagnosis, prognosis and treatment of ccRCC.